Comparative tumor promotion assessment of e‐cigarette and cigarettes using the in vitro Bhas 42 cell transformation assay. (26th April 2017) - Breheny, Damien; Oke, Oluwatobiloba; Pant, Kamala; Gaça, Marianna
Abstract : In vitro cell transformation assays (CTA) are used to assess the carcinogenic potential of chemicals and complex mixtures and can detect nongenotoxic as well as genotoxic carcinogens. The Bhas 42 CTA has been developed with both initiation and promotion protocols to distinguish between these two carcinogen classes. Cigarette smoke is known to be carcinogenic and is positive in in vitro genotoxicity assays. Cigarette smoke also contains nongenotoxic carcinogens and is a tumour promoter and cocarcinogen in vivo. We have combined a suite of in vitro assays to compare the relative biological effects of new categories of tobacco and nicotine products with traditional cigarettes. The Bhas promotion assay has been included in this test battery to provide an in vitro surrogate for detecting tumor promoters. The activity of an electronic cigarette (e‐cigarette; Vype ePen) was compared to that of a reference cigarette (3R4F) in the promotion assay, using total particulate matter (TPM)/aerosol collected matter (ACM) and aqueous extracts (AqE) of product aerosol emissions. 3R4F TPM was positive in this assay at concentrations ≥6 µg/mL, while e‐cigarette ACM did not have any promoter activity. AqE was found to be a lesssuitable test matrix in this assay due to high cytotoxicity. This is the first study to use the Bhas assay to compare tobacco and nicotine products and demonstrates the potential for its future application as part of a product assessment framework. These data add to growing evidence suggesting that e‐cigarettes may provide a safer alternative to traditional cigarettes. Environ. Mol. Mutagen. 58:190–198, 2017. © 2017 Wiley Periodicals, Inc.